Content learning in Japanese and English medium instruction: comparing chemistry learning outcomes in Japanese higher education - Aizawa, I (2021)
English Medium Instruction (EMI) is rapidly gaining momentum in line with internationalisation of higher education trends. However, this growth in provision is outpacing empirical research. Research has reported the lack of evidence on the impact of the medium of instruction on students’ content learning outcomes. This study thus drew comparisons between EMI students (n=27) and Japanese medium instruction (JMI) students (n=26) in terms of their directly measured and self- perceived content knowledge acquisition. Data were collected at a research site university where the Chemistry courses were available in both Japanese and English as part of a parallel program offering the same curriculum in either of two languages of instruction. An analysis was made of students’ content learning outcomes measured by a novel pre-post course content tests created by the EMI Chemistry professor for the purpose of the research. These measurable test outcomes were triangulated with data from student interviews to identify further differences in their perceived learning experience according to the language of instruction. These student interviews in addition to teacher interviews and lecture observations were used subsequently to discern the differences in the EMI and JMI course implementation as well as to elucidate academic challenges associated with medium of instruction. Subsequently, factors previously attested as crucial for content learning through EMI, such as proficiency, challenges, and prior content knowledge were explored to investigate the impact of these factors on students’ success in content learning in the EMI program. Methodologically, this study responds to calls for quasi-experimental research by adopting a longitudinal design of a course over three months, pairing in-depth quantitative analysis of the pre-post test scores with teacher and student interviews and lecture observations. The study found that while the quantitative findings unveiled no differences in content learning outcomes according to the medium of instruction, the qualitative evidence revealed that EMI students encountered a greater level of challenges than their JMI counterparts. The study also found that EMI students with lower English language proficiency faced considerably more onerous challenges than their more proficient counterparts when learning through EMI. Meanwhile, a range of factors also emerged as crucial facilitators for success in EMI, such as previous exposure to EMI education, motivation, revision and preparation, and learning strategies. This study will be one of the first attempts to investigate the effects of the medium of instruction on students’ content learning outcomes in Japan.